2020
DOI: 10.1177/2158244020924036
|View full text |Cite
|
Sign up to set email alerts
|

Rural Transportation Conference Participants’ Opinions and Concerns Pertaining to Transit for Older Adults

Abstract: Mobility remains a vital part of the well-being of rural-living, older adults and transportation disadvantaged persons. This study seeks to identify research and policy needs related to rural transit for older people and the transportation disadvantaged. To obtain this goal, the multidisciplinary study team conducted two activities as part of a 2016 rural transportation conference: a survey of conference attendees and open discussion to elicit additional information. Results suggest the attendees felt the need… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Results may differ based on the types of trip provided, the geographic and demographic characteristics of the service area, and characteristics of the service provided. Mjelde et al ( 12 ) also argued that many of the previous evaluation studies are flawed conceptually, use incorrect methods or assumptions, or both. TCRP Synthesis 128 concluded that these studies vary widely in their rigor and that there is still some confusion over the different types of study, their terminology, and interpretations ( 13 ).…”
mentioning
confidence: 99%
“…Results may differ based on the types of trip provided, the geographic and demographic characteristics of the service area, and characteristics of the service provided. Mjelde et al ( 12 ) also argued that many of the previous evaluation studies are flawed conceptually, use incorrect methods or assumptions, or both. TCRP Synthesis 128 concluded that these studies vary widely in their rigor and that there is still some confusion over the different types of study, their terminology, and interpretations ( 13 ).…”
mentioning
confidence: 99%